2018
DOI: 10.1002/ar.24016
|View full text |Cite
|
Sign up to set email alerts
|

The Neuropilin‐1 Ligand, Sema3A, Acts as a Tumor Suppressor in the Pathogenesis of Acute Leukemia

Abstract: Semaphorin‐3A (Sema3A) and vascular endothelial growth factor (VEGF165) are ligands of neuropilin‐1 (NRP‐1 or CD304) and are related to immunoregulation and tumor angiogenesis, respectively. However, possible interactions between NRP‐1 and Sema3A and VEGF165 in acute leukemia remain unclear, especially whether Sema3A plays a role in acute leukemia. In this study, both of the proportion of regulatory T cells (Tregs) and their expression of NRP‐1 were found to increase in acute leukemia patients compared with he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…Indeed, it was recently reported that a mutated sema3A, that unlike natural sema3A binds directly to the plexin-A4 receptor and not to neuropilin-1, is a better inhibitor of angiogenesis as compared to wild type sema3A and strongly inhibits the progression of pancreatic cancer in mouse models [89]. Interestingly, it was recently found that sema3A may also function as an inhibitor of the development of hematological malignancies such as multiple myeloma and various forms of leukemia and that this activity is likely also due to its anti-angiogenic activity [90,91,92].…”
Section: Class-3 Semaphorins As Regulators Of Tumor Progressionmentioning
confidence: 99%
“…Indeed, it was recently reported that a mutated sema3A, that unlike natural sema3A binds directly to the plexin-A4 receptor and not to neuropilin-1, is a better inhibitor of angiogenesis as compared to wild type sema3A and strongly inhibits the progression of pancreatic cancer in mouse models [89]. Interestingly, it was recently found that sema3A may also function as an inhibitor of the development of hematological malignancies such as multiple myeloma and various forms of leukemia and that this activity is likely also due to its anti-angiogenic activity [90,91,92].…”
Section: Class-3 Semaphorins As Regulators Of Tumor Progressionmentioning
confidence: 99%
“…Neuropilin-1 (NRP1) is a trans-membrane glycoprotein that function as a co-receptor for multiple extracellular ligands such as semaphorins, hepatic growth factor, FGF and TGF-β 5,6 . Mounting evidence has showed that NRP1 exert a critical role in tumorigenesis and metastasis 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…Folic acid deficiency correlates with elevated homocysteine levels, which is a risk factor for colon cancer [ 1 , 32 ]. Larriba et al [ 33 ] reported that colon cancer tissues that co-express Snai2 and Snai1 downregulated the vitamin D receptor, which mediates the antitumoral action of vitamin D. Sema3A is a ligand of neuropilin-1 and a tumor suppressor in acute leukemia [ 34 ]. Neuropilin-1 is involved in diverse processes, including cancer and angiogenesis [ 35 37 ].…”
Section: Discussionmentioning
confidence: 99%